Emotions and Loneliness in a Networked Society 2019
DOI: 10.1007/978-3-030-24882-6_8
|View full text |Cite
|
Sign up to set email alerts
|

Making Sense of The Lonely Crowd, Today: Youth, Emotions and Loneliness in a Networked Society

Abstract: The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific statement, that such names are exempt from the relevant protective laws and regulations and therefore free for general use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Excessive SMU and time spent browsing the web are positively associated with loneliness and negatively related to life satisfaction, as indicated by cross-sectional findings [ 44 ]. Among high school students from Portugal, those who spend free time on social networks and simultaneously enjoy being alone were not satisfied with their life [ 32 ]. Instagram addiction was directly negatively related to life satisfaction and positively to loneliness.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Excessive SMU and time spent browsing the web are positively associated with loneliness and negatively related to life satisfaction, as indicated by cross-sectional findings [ 44 ]. Among high school students from Portugal, those who spend free time on social networks and simultaneously enjoy being alone were not satisfied with their life [ 32 ]. Instagram addiction was directly negatively related to life satisfaction and positively to loneliness.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the positive association between Instagram use and loneliness was found among Turkish male high school students only, while this link was insignificant for females [35]. The other studies also found a marginally stronger association between SMU and loneliness in men than in women [31,32]. In contrast, female gender (β = 0.42), and higher social media use disorder (β = 0.03) were predictors of loneliness among Lebanese adults [36].…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations